Reconceptualising seaweed cultivation in China: climate law and policy implications - Keyuan Zou; Lei Zhang (Carbon Management)
The Chinese goal to reach carbon peak by 2030 and achieve carbon neutrality by 2060 (the “30/60” dual carbon goal) will require a swift and dramatic reduction in greenhouse gas emissions. Among various ocean carbon dioxide removal (CDR) technologies, seaweed cultivation has gained more attention due to its potential for CO2 removal. However, the current legal framework in China lacks specific laws and regulations addressing seaweed cultivation for carbon removal. This paper highlights three key points: (1) the existing Chinese legal system needs to be updated to keep up with policy changes and govern the practice of seaweed cultivation for carbon removal; (2) transitioning seaweed cultivation from aquaculture to an ocean CDR approach can promote climate mitigation benefits; and (3) successful implementation requires not only technical and financial support but also the establishment of comprehensive policy and legal frameworks.